Exposición materna al humo de tabaco ambiental y su relación con el peso de recién nacidos del Hospital Isidro Ayora - Carreño Oliveros, Génesis Estefanía (2015)
A maternal secondhand smoke study was made, with the purpose to know frequency and the relation of newborns weight, most frequent place of exposure, pregnant women age and the newborns sex of pregnant women who was exposed to secondhand smoke. It is a descriptive and cross-sectional study, the sample included 110 pregnant women hospitalized for labor at term in Gynecologic and Obstetrics service at Isidro Ayora Hospital. The information was collected of polls applied on pregnant women and the weight, sex and gestational age of newborns was taken of each Perinatal Medical Record. As a result it was found that there is a relation between the secondhand smoke exposure and the newborns weight p-0.000, in this study 49.1% of pregnant women were exposed to secondhand smoke during pregnancy, and their home was the main source of exposure. The age group of exposed pregnant women was between 15-19 years. Also, it was found a low percentage of low-birth-weight newborns of unexposed mothers and the most affected gender was male newborns. Keywords: Environmental Tobacco Smoke, maternal exposure, newborn weight.